Loneliness and its impact on the psychological well-being of Indonesian students abroad: A cross-cultural perspective - Ashilah, Nisa; Edy, Dewi Fatmasari (Journal of Psychological Perspective, 2025)
The increase in the number of international students from Indonesia continues. Cultural and environmental differences between home countries and study destinations present significant challenges, one of which is loneliness, which is a common problem among students. Studies show that loneliness affects the mental and academic health of international students, including those from Indonesia. Therefore, this study aims to examine the role of loneliness on psychological well-being and its six dimensions in Indonesian students studying abroad. This study used a quantitative correlational approach, with the research instruments being the UCLA Loneliness Scale and the Psychological Wellbeing Scale. A total of 214 participants were selected through purposive sampling and analysed using multiple linear regression analysis techniques. The results showed that the majority of participants had low levels of loneliness (79.4%) and high psychological well-being (69.2%). Furthermore, loneliness had a negative role on each dimension of psychological well-being and overall psychological well-being with a range of 0.232-0.518. Thus, it can be concluded that the lower the loneliness of university students, the higher their psychological well-being and conversely. The findings imply the need to increase students' awareness of psychological health and the active role of student organisations in facilitating self-adjustment and strengthening social relationships to maintain the psychological well-being of Indonesian students abroad.